Sub-chronic and developmental toxicity of transdermal delivery of Renzhu ointment in young SD rats. (3rd July 2022) - Yang, Fuzhen; Cao, Mengfei; Zhong, Lian; Xiao, Ni; Chen, Guanfeng; Cao, Qian; Huang, Fengke; Zhang, Jun; He, Huifen
Abstract: Purpose: Renzhu ointment (Renzhuqigao, RZQG) is a patented herbal drug derived from Chinese traditional medicine formula and modern clinical experience for the transdermal treatment of non-infectious infantile diarrhoea. The safety of RZQG in preclinical studies has not been reported. Materials and methods: In this study, the pups of parent rats were examined for sub-chronic toxicity and developmental toxicity. After 21 days of birth, they were exposed to RZQG through their abdominal skin at doses of 0.1, 0.3, and 0.9 g/kg/day for 4 weeks and then were observed for another four weeks during their recovery period. Results: During the administration period, RZQG had no significant toxicological effect on body weight, food consumption, external eye examination, urinalysis, bone marrow examination, histopathology, central nervous system, reproductive system, or skeletal development. However, in the 0.9 g/kg/day group, the skin of some rats became dry and cracked, red and swollen, forming a white scab, while the white blood cells (WBC) count in female rats was lower and cholesterol (CHOL), triglycerides (TG), and glutamyl-transferase (GGT) were higher ( p  < 0.05). Conclusions: Rats receiving 0.9 g/kg/day exhibited skin irritation and were suspected to have a mild liver injury. There was no evidence of delayed toxicity four weeks after withdrawal. Therefore, the no-observed adverse effect level of RZQG was 0.3 g/kg/day (30 times the clinical dose planned and 4.92 times the human equivalent dose).